Effects of ginkgo biloba extract on laser-induced choroidal neovascularization in rats - Chao Chen (Guoji Yanke Zazhi, 2013)
AIM: To investigate the effects of ginkgo biloba extract(EGb 761)on laser-induced choroidal neovascularization(CNV)in rats. METHODS: Totally 60 BN rats were randomly divided into 4 groups: normal control group, model group, experimental group, physiological saline group with 15 in each group. All CNV models were made by krypton laser. Rats in experimental group were intraperitoneally injected with 0.35% EGb761(100mg/kg)every day after laser exposure until they were sacrificed. Rats in physiological saline group were intraperitoneally injected physiological saline every day after laser exposure until they were sacrificed. Fundus fluorescein angiography(FFA)was performed on every rat on the 7th day, 14th day and the 21st day after laser exposure, then the rats were sacrificed immediately. The eyes were enucleated and processed for histopathologic examination. RESULTS: There was no choroidal fluorescein leakage staining in normal rats. There were obviously less choroidal fluorescein leakage points in experimental groups than that in the corresponding model groups(P<0.05), the difference had statistical significance. The structures of the retina and choroid were preserved better in experimental group than that in the model group. CONCLUSION: EGb761 len inhibit the formation of laser-induced CNV in rats. The longer the time, the better curative effect.